Pengaruh Media Kartu Kata Bergambar Terhadap Kemampuan Mengenal Huruf Abjad Pada Anak Usia 4-5 Tahun Di TK Bina Vita Palembang - Wulandari, Inge Pricillia; Febriyanti, Febriyanti; Sartika, Indah Dwi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This research is entitled "The Effect of Picture Card Media on the Ability to Recognize Alphabets in Children Aged 4-5 Years at TK Bina Vita Palembang". The problem in this study is the low ability to recognize alphabets. This study aims to determine the application of picture card media on the ability to recognize alphabets, the ability to recognize alphabets after being given picture card media, and to determine the effect of picture card media on the ability to recognize alphabets in children aged 4-5 years at TK Bina Vita  Palembang. This type of research is quantitative with a pre-experimental design experimental research method. The design of this study uses One Group Pretest - Posttest Design. The population of this study was group A children totaling 17 children at TK Bina Vita Palembang. Data collection techniques used observation, testing, and documentation techniques. Data analysis techniques in this study used validity tests, reliability tests, normality tests, homogeneity tests, and hypothesis tests using t-tests. The hypothesis results were obtained after the initial test (pretest) and final test (posttest), then the researcher analyzed the results of the study. The results of data analysis in proving the hypothesis test obtained tcount = 31.498 while dk = 17-1 = 16 level of 5% so that it was obtained for ttable = 1.74588 because tcount > ttable (31.498> 1.74588) then HO is rejected and Ha is accepted. This means that there is an influence of picture word card media on the ability to recognize letters of the alphabet in children aged 4-5 years at TK Bina Vita Palembang.